Analysis Of Android-Based Online Message Gateway Towards The Use Of Plastic Bags - Muhammad Ali Sodik; Dhea Maulina Salam; Sri Kardjati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Plastic bags is increasing with the development of technology, industry and population. Community dependence on plastic products is indeed very large. It is undeniable that there are many plastic based equipment that are sold at relatively cheap prices. Therefore socialization or education to reduce the use of plastic bags should be intensified. the researchers used an approach with the Android Based Online Message Gateway. The research design used was pre experimental design. With a population of 64, simple random sampling technique so that a sample of 56 respondents. Using the Wilcoxon statistical test with a significance level of 0.05. The results showed that the significance value of the attitude variable 0,000 <0.05 and the significant value of the action variable 0,000 <0.05. So, if Ho and H1 are rejected, then there is the influence of Android Based Online Message Gateway on Attitudes and Action in the Use of Plastic Bags.